2006
DOI: 10.1016/j.cell.2006.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of bxd Noncoding RNAs Promoted by Trithorax Represses Ubx in cis by Transcriptional Interference

Abstract: Much of the genome is transcribed into long noncoding RNAs (ncRNAs). Previous data suggested that bithoraxoid (bxd) ncRNAs of the Drosophila bithorax complex (BX-C) prevent silencing of Ultrabithorax (Ubx) and recruit activating proteins of the trithorax group (trxG) to their maintenance elements (MEs). We found that, surprisingly, Ubx and several bxd ncRNAs are expressed in nonoverlapping patterns in both embryos and imaginal discs, suggesting that transcription of these ncRNAs is associated with repression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
286
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(310 citation statements)
references
References 48 publications
(75 reference statements)
16
286
1
5
Order By: Relevance
“…The transcription of noncoding RNAs (ncRNAs) seem to play an important, although diverse, role in the regulation of the BX-C. Petruk et al (42,43) found that noncoding transcription through the bxd PRE is crucial for Ubx repression and that transcription through Mcp overlaps with AbdB transcription in the embryo. Work from others and our laboratory showing that ncRNA transcription in the AbdB domain coincides with an active AbdB gene indicates a nonuniversal, gene specific function for ncRNAs in the BX-C (31,43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription of noncoding RNAs (ncRNAs) seem to play an important, although diverse, role in the regulation of the BX-C. Petruk et al (42,43) found that noncoding transcription through the bxd PRE is crucial for Ubx repression and that transcription through Mcp overlaps with AbdB transcription in the embryo. Work from others and our laboratory showing that ncRNA transcription in the AbdB domain coincides with an active AbdB gene indicates a nonuniversal, gene specific function for ncRNAs in the BX-C (31,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Trx-and TAC1-interacting histone acetyltransferases may then be responsible for setting epigenetic marks that maintain the active transcription state. Petruk et al (42) showed that Trx is required for transcription elongation and that it is localized in the gene body of active Ubx, caused by the interaction with elongation factors. In contrast, Papp and Muller (16), who investigated the distribution of PcG and TrxG proteins at the active and repressed Ubx gene in imaginal discs, found the same restricted Trx profile as we did, namely Trx binding at discrete sites.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that bxd acts in trans to recruit histone methyltransferases to Ubx enhancer elements and thus promotes stable activation of transcription (SanchezElsner et al, 2006). Other groups, however, have claimed that bxd has no effect in trans, but instead acts in cis via transcriptional interference to prevent recruitment of trithorax proteins to the enhancer elements, and thus represses expression of Ubx (Petruk et al, 2006).…”
Section: How Might Osts Work?mentioning
confidence: 99%
“…NURF facilitates active chromatin by repositioning nucleosomes along DNA (Sims and Reinberg, 2006). TrxG also promotes expression of the Hox gene Ubx by facilitating transcriptional elongation (Petruk et al, 2006). These findings may explain how trxG regulates gene activation.…”
Section: Trithorax Group Promotes Active Chromatinmentioning
confidence: 94%